l-Canavanine Metabolism in Jack Bean, Canavalia ensiformis (L.) DC. (Leguminosae) - Rosenthal, Gerald A. (1982)
l-Canavanine, a highly toxic arginine antimetabolite, is the principal nonprotein amino acid of many leguminous plants. Labeled-precursor feeding studies, conducted primarily with [(14)C]carbamoyl phosphate, and utilization of the seedlings of jack bean, Canavalia ensiformis (L.) DC. (Leguminosae), have provided evidence for l-canavanine biosynthesis from l-canaline via O-ureido-l-homoserine. This reaction pathway appears to constitute an important in vivo route of canavanine production. Canavanine cleavage to canaline may represent a degradative phase of canavanine metabolism distinct from the anabolic reactions described above. Thus, while these reactions of canavanine metabolism bear analogy to the mammalian Krebs-Henseleit ornithine-urea cycle, no evidence has been obtained at present for the reutilization of canaline in ureidohomoserine formation.